The Effect Of Digital Influencers On Cosmetic Dental Preferences: Trends, Motivations, And Outcomes, A Systematic Review - Abid, Maryam; Altaf, Maria; Damni, Damni; Khawer, Maham; Tahir, Araib; Rehman, Amna (Journal of Neonatal Surgery, 2025)
Background:This systematic review examines the effect of digital influencers on cosmetic dental preferences, exploring trends, motivations, and outcomes. Recent research indicates that social media platforms, especially Instagram and TikTok, have significantly shaped dental aesthetics, 68% of users reporting more inclined towards cosmetic dental procedures influenced by digital personalities. Objective:The objective is to assess the role of influencers in shaping patient motivations for cosmetic dentistry, particularly the rising demand for procedures such as veneers and teeth whitening. Methodology:A systematic literature search was conducted using PRISMA guidelines, with data extracted from studies published between 2018 and 2024. Meta-analysis was performed using RevMan software to synthesize results across 15 studies, involving over 10,000 participants globally. Results:Results revealed that 72% of patients were motivated by influencers' posts, directly impacting their choice of cosmetic dental treatments. Conclusion:The conclusion suggests that digital influencers play a crucial role in shaping modern cosmetic dental trends, highlighting the need for ethical considerations in promoting dental services online